2022
DOI: 10.3390/rs14040826
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Street Lighting Quality in Residential Areas by Combining Remote Sensing Tools and a Survey on Pedestrians’ Perceptions of Safety and Visual Comfort

Abstract: The perceived quality of street lighting influences pedestrians’ perceptions of safety and visual comfort, as well as outdoors activities at night. This study explores the association between street lighting attributes, such as illuminance and wavelength, and pedestrians’ feeling of safety (FoS) and perceived lighting quality (PLQ) in eight residential districts in Dalian, China. To achieve this goal, we combine remote sensing technology with ground investigation. The ground research includes physical measurem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 34 publications
1
17
0
2
Order By: Relevance
“…Yet, most real scene experiments (27) were performed during wintertime in cold-climate zones, such as in the UK (e.g., S. Fotios et al, 2019), Scandinavian countries (e.g., Patching et al, 2017; Rahm & Johansson, 2021), or northern China (e.g., Z. Lin et al, 2023; Liu et al, 2022); while only a handful were performed in warmer climates, such as in Malaysia (Hamsa et al, 2009) or Israel (Svechkina et al, 2020), in which a higher plateau threshold for safety was reported. Plateau threshold was also found to vary with location, or more specifically—with city characteristics, as observed by Svechkina et al (2020) and Liu et al (2022).…”
Section: Resultsmentioning
confidence: 99%
“…Yet, most real scene experiments (27) were performed during wintertime in cold-climate zones, such as in the UK (e.g., S. Fotios et al, 2019), Scandinavian countries (e.g., Patching et al, 2017; Rahm & Johansson, 2021), or northern China (e.g., Z. Lin et al, 2023; Liu et al, 2022); while only a handful were performed in warmer climates, such as in Malaysia (Hamsa et al, 2009) or Israel (Svechkina et al, 2020), in which a higher plateau threshold for safety was reported. Plateau threshold was also found to vary with location, or more specifically—with city characteristics, as observed by Svechkina et al (2020) and Liu et al (2022).…”
Section: Resultsmentioning
confidence: 99%
“…5D 模型, 即密度(density)、 多样性(diversity)、 设计 (design)、 公共交通可达性(distance to transit)和目的 地可达性(destination accessibility) [31] , 并借助街景图 片数据增加了微观尺度指标, 从可达性、 吸引力和 友好性 3 个维度分解建成环境, 形成二维和三维相 结合的指标体系, 具体内容如表 1 所示。需要注意 的是, 相对于吸引力和友好性而言, 可达性在 "自 存" 与 "共存" 需求方面存在冲突点, 即个体希望目 的地距离变近和公共设施需要为更多的人提供服 务之间的矛盾 [32] , 而在个体可以接受的距离范围内 提升目的地自身的服务效率和周边的通行能力, 可 能是解决该冲突点的有效方式。当目的地趋近于 为每个人提供良好的出行服务时, 个体便可以接触 到更多的活动场所或融入多种活动人群之中, 进而 对增加日常活动机会有一定的促进作用。因此, 本 文将 "邻里" 作为个体 "自存" 的目的地可达范围, 在 可达性测量上突出 "共存" 需求, 主要包括目的地的 区位条件指标 [33] 和通行难易程度指标 [34] 。另外, 吸 引力测量选取环境品质和微观设计指标 [35][36] ; 友好 性测量选取道路连通性和公交便捷性指标 [37] , 以及 安全设施布局水平指标 [38] 。 在日常活动方面, Reichman [39] 将个体出行活动 分为为强制性活动(mandatory activities)、 维护性活 动(maintenance activities)和可支配活动(discretion- 设计适宜性的重要指标, 有研究表明, 适宜的天空 开阔度对老年人的情绪健康有积极作用 [43] ; 台阶占 通过休闲娱乐等活动来获得 [45] 。但是, 休闲娱乐活 动属于非必要性活动 [46] Understanding the relationships between the physical environment and physical activity in older adults: A system-…”
Section: 在建成环境指标选取方面, 基于广泛被应用的unclassified
“…Temperatur warna yang digunakan dalam perencanaan yaitu warmwhite atau putih kekuningkuningan. Dengan menggunakan lampu berwarna kuning akan meningkatkan rasa aman dan nyaman bagi pengguna jalan [8].…”
Section: Pendahuluanunclassified